Theory and method in higher education research - Huisman, Jeroen; Tight, Malcolm (Theory and Method in Higher Education Research Ser., 2022)
"This volume explores several topics including critical race theory; the use of communities of practice theory; participant ethnography, and decolonization using indigenous principles." -- back of cover.